2015
DOI: 10.1007/s11104-015-2492-7
|View full text |Cite
|
Sign up to set email alerts
|

No depth-dependence of fine root litter decomposition in temperate beech forest soils

Abstract: Aims Subsoil organic carbon (OC) tends to be older and is presumed to be more stable than topsoil OC, but the reasons for this are not yet resolved. One hypothesis is that decomposition rates decrease with increasing soil depth. We tested whether decomposition rates of beech fine root litter varied with depth for a range of soils using a litterbag experiment in German beech forest plots. Methods In three study regions (Schorfheide-Chorin, Hainich-Dün and Schwäbische-Alb), we buried 432 litterbags containing 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…This finding corroborates several shorter-term (12-36 month) studies that did not find decomposition differences in a common substrate among soil horizons (Fujii and Takeda 2010) or depths (Sanaullah et al 2011;Solly et al 2015). Similarly, traditional litter decomposition studies have found that within an ecosystem or among similar ecosystems, litter type explains most of the variation in mass loss (e.g.…”
Section: The Effect Of Litter Typesupporting
confidence: 90%
“…This finding corroborates several shorter-term (12-36 month) studies that did not find decomposition differences in a common substrate among soil horizons (Fujii and Takeda 2010) or depths (Sanaullah et al 2011;Solly et al 2015). Similarly, traditional litter decomposition studies have found that within an ecosystem or among similar ecosystems, litter type explains most of the variation in mass loss (e.g.…”
Section: The Effect Of Litter Typesupporting
confidence: 90%
“…At depth, a lack of fresh labile carbon inputs limits the energy that microbes have to produce the enzymes they need to decompose recalcitrant carbon sources (Fontaine et al 2007). Interestingly, while Solly et al (2015) and Sanaullah et al (2011) also report similar longer term decomposition rates across depths, the dominant factors that control decomposition (e.g. abiotic vs. abiotic limitations) differed across depths.…”
Section: Discussionmentioning
confidence: 91%
“…Soil depth affects root litter decomposition rates in some studies (Rovira and Vallejo 1997;Gill and Burke 2002;Garcia-Pausas et al 2012;Berhe 2012), but not all (Weaver 1947;Sanaullah et al 2011;Solly et al 2015). Compared to topsoil, subsoil has a lower microbial biomass concentration and fungi:bacteria ratio (Stone et al 2014), lower root density and less rhizosphere volume, reduced connectivity between SOC moieties, and greater protection of organic matter by aggregates and mineral particles (Schrumpf et al 2013), all of which tend to reduce microbial activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the definition of community responses to changing litter properties and the untangling of potential underlying mechanisms are complicated by the spatially heterogeneous distribution of fungi in forest soils (Lindahl et al, 2007;Davison et al, 2012;Weber et al, 2013). The spatial scale at which fungal taxa colonize litter and soil differs considerably between groups of fungi, and depends on the local physical and chemical conditions, which vary within a soil profile and depend on the plant species present (Finzi et al, 1998;Neville et al, 2002;Fierer et al, 2003;Cools et al, 2014;Clemmensen et al, 2015;Solly et al, 2015;Sterkenburg et al, 2015). Moreover, the fungal community composition is commonly stratified according to distinct functional groups occupying different soil horizons (Lindahl et al, 2007;Baldrian et al, 2012;Clemmensen et al, 2015;B€ odeker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%